Effect of Product Quality and Promotion Mix on Coca Cola Purchase Decition - Nadirah, Andi; Risal, M.; Ikhwan, Nira (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The product is one of the elements of the marketing mix, which determines how the brand can compete in the market. In addition, of course, it must be supported by the right advertising mix to present products to consumers. As a well-known beverage brand, Coca-Cola must pay attention to these two factors in order to remain in the market. Based on this, it is determined whether product quality and advertising mix influence the purchase decision of Coca-Cola beverages in Bone-Bone District, North Luwu Regency. The variables used in this study were product quality, promotion mix and purchase decision. The research method used is a quantitative method with a sampling technique used in this study, namely a non-probability sampling technique with a purposive random sampling method, which is random sampling with a specific purpose. Population determination using Lameshow's formula is 96.4 and rounded up to 100 respondents. Data collection was carried out through questionnaires and processed using the SPSS 21 statistical program. The results showed that product quality has a close relationship to the decision to purchase Coca-Cola beverages in Bone-Bone District, North Luwu Regency, with a very strong significance value. The results of this study found that the promotion mix positively and significantly influenced the purchase decision of Coca-Cola beverages in Bone-Bone District, North Luwu Regency. The results of the study can be concluded based on the level of significance which shows that product quality and promotion mix have a positive and significant effect on purchasing decisions. Keywords: coca cola consumer, marketing mix, product quality, purchase decision